REKAYASA EKONOMI KONSUMSI BERBASIS HADIS MI’DAH: IMPLIKASI EFISIENSI FINANSIAL PRIBADI RUMAH TANGGA DAN PENGUATAN STABILITAS EKONOMI MASYARAKAT - Raden Ayu Ritawati; Raden Ayu Erika Septiana (CV. Cendekiawan Muda Sriwijaya, 2026)
Excessive consumption patterns not only have the potential to weaken household financial resilience but are also associated with increased health risks and broader economic burdens on society. Islam offers a principle of consumption moderation through the prohibition of israf in the Qur’an and the guidance on proportional stomach capacity found in the Hadith of Mi’dah. This study aims to analyze the application of consumption moderation based on the Hadith of Mi’dah in improving the efficiency of household food expenditure and to develop a simulation of financial surplus utilization to support the wider community economy. This study employed a mixed-methods approach using a sequential exploratory design. The first stage applied a qualitative approach through thematic interpretation of Qur’anic verses, the Hadith of Mi’dah, and Islamic economics literature. The second stage employed a one-group pretest–posttest pre-experimental design involving 30 Muslim household heads in the urban area of Palembang, with monthly household incomes ranging from IDR 5,000,000 to IDR 10,000,000. The intervention was conducted over 30 days by controlling meal portions and reducing the consumption of non-essential food items. The descriptive findings indicate that average monthly food expenditure decreased from IDR 2,750,000 to IDR 1,850,000, resulting in savings of IDR 900,000 per household and an efficiency rate of 32.7%. The largest reduction occurred in lifestyle-related food expenditure, including snacks, fast food, and café consumption. A simulation of the allocation of part of the financial surplus shows the potential to mobilize IDR 4,500,000 per month in ZISWAF funds and IDR 12,000,000 per month in sharia-compliant investments from the 30 participating households. These findings suggest that the Hadith of Mi’dah can be conceptualized as a principle of consumption moderation that supports the protection of life and wealth. Nevertheless, its effects on public health, employment creation, and the reduction of the burden of public healthcare financing remain potential rather than empirically established outcomes. Further studies employing larger samples, longer research periods, and more robust research designs are therefore required.